The influence of organizational strategic plan implementation and its relationship with secondary school academic achievement in Selangor - Jaafar, Mariani; Asimiran, Soaib; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2022)
The academic excellence of the school is the main target of the Malaysian Education Blueprint (MEBP) 2013-2025 to compete, and be at par with, the world's best education by the year 2025. In order to fulfill this desire, it is important for school leaders to form and implement organizational strategic plan effectively at school level to guarantee the excellence of the school's academic achievements. However, there is a lack of studies that examine the relationship between these variables, especially at the local level. Therefore, this study is conducted to determine the level of implementation of the organizational strategic plan and its relationship with the school's academic achievement. A cross-sectional survey method was used in the data collection process. A total of 420 subject teachers who were randomly selected from 39 secondary schools in Selangor, Malaysia. Data were analyzed descriptively and inferentially using IBM SPSS version 25 and AMOS version 24 software. The descriptive analysis shows that the level of implementation of the organizational strategic plan was high (M=5.13, SP=0.60) and the school's academic achievement level was satisfactory (M=5.15 , SP=0.90). The SEM test shows that the relationship between the organizational strategic plan and the school's academic achievement is significant at a positive value (?=0.140, p<0.05). The analysis found that the implementation of the plan still has a positive effect on the school's academic achievement even though the effect is small. There are some weaknesses in the planning stage that need to be overcome immediately by the principal in order to for the academic achievement of the school to gain optimal effects. It is expected that principals are given continuous courses and training to improve their knowledge and strategic management skills. Future studies suggested to be conducted in qualitative study to obtain more in-depth information regarding the process of implementing the strategic plan of the school organization, identifying the constraints faced by principals in implementing the plan as well as identify factors that can influence the effectiveness of school planning and academic achievement. It is also suggested that future studies involve schools throughout Malaysia.